Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 6 - Section 6.2 - Adding and Subtracting Rational Expressions - Exercise Set: 107



Work Step by Step

RECALL: $\\x^{-m}=\dfrac{1}{x^m},m \gt 0$ Use the rule above to have: $\\=4\left(\frac{1}{x^2}\right) - 3\left(\frac{1}{x}\right) \\=\dfrac{4}{x^2} - \dfrac{3}{x}$ Make the expressions similar using the LCD which is $x^2$ to have: $\\=\dfrac{4}{x^2} - \dfrac{3(x)}{x(x)} \\=\dfrac{4}{x^2} - \dfrac{3x}{x^2} \\=\dfrac{4-3x}{x^2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.